“The Study of Bacteriological Agents of Chronic Suppurative Otitis Media Aerobic Culture and Antibiotic Sensitivity Testing Pattern at a Tertiary Care Hospital in and around Rajamundry: A cross-sectional study” - Dr. Neelima Pantagada; Dr. Praveen Kavoori (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Chronic suppurative otitis media is a chronic infection of the middle ear and mastoid cavity which if not treated leads to partial or total loss of hearing and even life-threatening complications like meningitis and Intracranial abscess. Hence it is important to treat the persistent ear discharge in CSOM according to the antimicrobial sensitivity of the organism isolated.Methods: This is a prospective cross-sectional study done in 135 clinically diagnosed patients of CSOM at GSL medical college and General Hospital, Rajamundry, Andhra Pradesh from May 2019 to October 2019. Sterile swabs were used to collect pus from discharging ear and were inoculated onto Blood and MacConkey agar for 24-48 hrs, and identification of organisms was done by using standard biochemical reactions and antibiotic sensitivity testing done by using modified Kirby- Bauer method as per CLSI guidelines.Results: A total of 156 strains were isolated from 135 patients in the present study of which Pseudomonas aeruginosa and Staphylococcus aureus were amongst the most isolated pathogens in culture. Imipenem showed the most sensitivity against Pseudomonas, subsequently levofloxacin and piperacillin. Linezolid was the most sensitive versus Staphylococcus ensued by ciprofloxacin and cloxacillin.Conclusions: In the present study of Chronic suppurative otitis media patients, Pseudomonas and Staphylococcus were highly prevalent and showed increased resistance to beta-lactams and commonly used antimicrobial drugs. Antimicrobials like imipenem, piperacillin, and quinolones are effective against most cases of chronic suppurative otitis media. Successful treatment and avoidance of antimicrobial resistance would be achieved by the appropriate use of antimicrobials with sufficient evidence.